Enhancing the quality of life for physical therapists: insights from a cross-sectional study - Rahaf Eid Al Ali; Sahab A. Alrowaishd; Elaf Z. Abu Thyab; Raghad K. Almarzuqi; Manal I. Al Awaji; Monira I. Aldhahi; Zizi M. Ibrahim; Zizi M. Ibrahim (Frontiers Media S.A., 2024)
BackgroundPhysical Therapy profession is known for its demanding physical requirements. This increases the risk of attrition and work-related accidents and disorders that affect physical therapists' quality of life and work performance. This study aimed to evaluate the effect of physical activity level and other contributing factors on quality of life of physical therapists.MethodsA cross-sectional study was conducted among practicing physical therapists (n = 258). The International Physical Activity Questionnaires-Short Form was used to measure physical activity levels and the World Health Organization Quality of Life Questionnaire short form was used to measure the quality of life among physical therapists. Data was collected through a self-administered online survey using Microsoft Forms.ResultsThe eligible participants were 258 out of 297. The highest percentage of physical therapists had a moderate physical activity level (45.35%) and the median for overall quality of life score was 63.27(52.73-73.59). There was a significant positive correlation between physical activity and age with overall quality of life score (rs = 0.41, p < 0.001; rs = 0.13, p < 0.036) respectively and a significant negative correlation between body mass index and overall quality of life score (rs = −0.13, p < 0.04).ConclusionThe results obtained revealed that physical therapists mostly have moderate physical activity level and relatively good perceived quality of Life. Furthermore, our study identified significant correlations between physical activity, age, body mass index, and the overall quality of life among practicing physical therapists.